The epidemiology and pathophysiology of heart failure - Rathi, Shradha; Deedwania, Prakash C (The Medical clinics of North America, 2012)
Heart failure (HF) remains a major growing public health problem in the United States. Despite extensive understanding of the mechanism at the molecular level and innovations in therapy, HF carries high morbidity and mortality rates, with frequent hospital admissions. In the Medicare population, HF is the leading cause for hospitalization, accounting for more than1 million admissions per year. The authors provide a review of the epidemiology and pathophysiology of HF.